Advancing a constitutional approach in evaluating mergers and acquisitions in South Africa : lessons from competition commission of South Africa vs Mediclinic Southern Africa (PTY) LTD 2022 (4) SA 323 (CC) - Prof Munyai, Phumudzo (University of Pretoria, 2024)
Mini Dissertation (LLM (Consumer Protection))--University of Pretoria, 2024